Incorporation of nisin and oregano essential oil in cow’s milk to improve the quality of fresh cheese - Cama-Curasi, John Víctor (2022)
Firstly, this study aimed to determine the effect of adding nisin (0, 250 and 500 IU mL-1) and oregano essential oil (OEO) (0, 0.025% and 0.05%), alone or in combination, on Staphylococcus aureus load in cow’s milk. Next, it was evaluated the sensory, physicochemical and microbiological quality of fresh cheese (FC) manufactured with milk added of nisin + OEO (C1) or nisin alone (C2) compared to a control cheese (C0, milk without the addition of nisin or OEO). Results showed that adding nisin effectively reduced the S. aureus count in milk in a similar manner to adding way the combination of nisin + OEO compared to the control. FC quality evaluation results revealed that C1 and C2 did not alter the physicochemical quality of FC (pH, fat and total solids content) during storage (0-8 days) compared to the control. Furthermore, C1 and C2 reduced in a similar manner aerobic mesophilic bacteria and Enterobacteriaceae count in FC compared to the control during storage.  Sensory evaluation showed that consumers did not value FC added of nisin + OEO (C1) due to its intense aroma of oregano, rating it with the lowest global quality.